Easily adhesive polyester film
By forming a composition coating layer of polycarbonate polyurethane and blocked isocyanate C on the polyester film, the problem of degradation of adhesion in a high temperature and high humidity environment is solved, and efficient adhesion maintenance and equipment reliability are achieved.
Patent Information
- Application Number
- CN202380065820.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-09-05
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to maintain the adhesion between polyester film and functional layers such as hard coatings and adhesives for a long time in high temperature and high humidity environments, affecting the reliability of equipment such as liquid crystal TVs.
A composition containing polycarbonate polyurethane and blocked isocyanate system C is used as an easy-adhesomer chain, and a coating layer with high adhesion and flexibility is formed by adjusting the content of the n-hexamethylene chain and using urea formate, biurea or adduct of hexamethylene diisocyanate as a crosslinking agent.
The adhesion between the polyester film and the functional layer is significantly improved, especially the long-term maintenance ability in high temperature and high humidity environments, ensuring the reliability and stable performance of equipment such as LCD TVs.
Smart Images

Figure BDA0005309753630000201 
Figure BDA0005309753630000351
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated polyester film and more particularly to a highly adhesive polyester film which has excellent adhesion to various functional layers, anti-blocking properties, and transparency and is also suitable for optical applications. Background Art
[0002] A hard coat film having a transparent hard coat layer laminated thereon is used for the front surfaces of displays such as touch panels, computers, televisions, and liquid crystal display devices, and decorative materials.
[0003] In addition, liquid crystal panel components used in displays are laminated with a hard coat film and a polarizing plate or with other components, and adhesive components are applied during the lamination.
[0004] As the transparent plastic film as the base material, a transparent polyester film is generally used. In order to improve the adhesion between the base polyester film and the hard coat layer and the adhesive, a coating layer having high adhesion is often provided on the surface of the polyester film as an intermediate layer.
[0005] The hard coating film needs to have durability to temperature, humidity, light, transparency, chemical resistance, scratch resistance, antifouling, etc. In addition, since it is mostly used on the surface of displays and decorative materials, it is required to have visibility and design. Therefore, in order to suppress glare and rainbow colors caused by reflected light when viewed from any angle, an anti-reflection layer with a multilayer structure consisting of a high refractive index layer and a low refractive index layer stacked on top of the hard coating is usually provided.
[0006] In recent years, hard coatings with various chemical compositions have been developed, and the adhesion between the substrate and the hard coating is studied each time. Not only the initial adhesion immediately after lamination is required, but also moisture and heat resistance, adhesion retention, adhesion retention over time, etc. are required for the long-term use reliability of liquid crystal televisions using films laminated with hard coatings, and products with various resistances are required.
[0007] The same is true for the adhesive, which needs to have durability, transparency, chemical resistance, scratch resistance, antifouling properties, etc. to temperature, humidity, and light. In addition, since it is mostly used on the surface of displays and decorative materials, visibility and design are required. In recent years, adhesives with various skeletons have been developed, and the adhesion between the substrate and the adhesive is explored every time. Not only the initial adhesion just after lamination is required, but also the reliability of long-term use of LCD TVs using components bonded with adhesives, such as moisture and heat resistance, adhesion retention, and adhesion retention over time, is required, and a product with various tolerances is required.
[0008] In a liquid crystal display device, polarizing plates are arranged on both sides of a glass substrate forming the surface of a liquid crystal panel, based on its image formation method. A polarizing plate generally has the following structure: a polarizing plate protective film is attached to both sides of a polarizer formed of a polyvinyl alcohol-based film and a dichroic material such as iodine, with the aid of a hydrophilic adhesive such as a polyvinyl alcohol-based resin. As a protective film for protecting a polarizer, a triacetate cellulose film has been used in the past from the viewpoint of optical properties and transparency.
[0009] However, the durability of cellulose triacetate is insufficient. When a polarizing plate using a cellulose triacetate film as a polarizer protective film is used under high temperature or high humidity, the performance of the polarizing plate such as polarization degree and hue may decrease. In addition, in recent years, in order to cope with the thinning of displays, it is necessary to make the polarizing plate thinner, but from the perspective of maintaining water barrier properties, there is a limit to the thinning of cellulose triacetate film. For this reason, the use of polyester film as a polarizer protective film having durability and water barrier properties has been proposed (for example, refer to Patent Document 1).
[0010] The cellulose triacetate film used as a polaroid protective film is subjected to an alkali treatment on the surface, etc., and has a very high affinity with a hydrophilic adhesive. Therefore, the protective film formed by the cellulose triacetate film has a very high adhesion to the polaroid coated with a hydrophilic adhesive. However, the adhesion of the polyester film to the hydrophilic adhesive is insufficient, especially in the case of a polyester film with orientation through a stretching treatment, this tendency is more significant. For this reason, in order to improve the adhesion to the polaroid or the hydrophilic adhesive coated on the polaroid, a highly hydrophilic material such as the easy-adhesion layer disclosed in Patent Document 1 is used to coat the surface of the polyester film.
[0011] In the field of conventional highly adhesive polyester films, a polyester resin having a naphthalene dicarboxylic acid component is used for a coating layer having highly adhesive properties, and the polyester resin has excellent adhesion to a substrate polyester film, and this is proposed as a suitable example (e.g., see Patent Document 2). In addition, a method of using a polyurethane resin having a polycarbonate component as a resin having excellent flexibility and high adhesion is proposed (e.g., see Patent Document 3).
[0012] However, although the adhesion was confirmed in all of them, a highly adhesive polyester film which can guarantee the adhesion after long-term storage has not yet been obtained.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Publication No. 2013-063610
[0016] Patent Document 2: Japanese Patent Application Publication No. 2011-246663
[0017] Patent Document 3: Japanese Patent Application Publication No. 2011-168053 Summary of the invention
[0018] Problem that the invention aims to solve
[0019] The present invention is made against the background of the above-mentioned problems of the prior art. That is, the purpose of the present invention is to provide an easily adhesive polyester film having improved adhesion between functional layers such as a hard coat layer and an adhesive and a polyester film as a substrate, and to provide an easily adhesive polyester film suitable for optical applications, etc.
[0020] Solutions for solving problems
[0021] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have arrived at the present invention.
[0022] That is, the present invention includes the following configurations.
[0023] 1. An adhesive polyester film, comprising a coating layer on at least one surface of the polyester film, wherein the coating layer is formed from a composition comprising polycarbonate polyurethane and a blocked isocyanate C, wherein the blocked isocyanate crosslinking agent is selected from an allophanate, a biuret or an adduct of hexamethylene diisocyanate, and the content of normal hexamethylene chains present at the α-position of carbonate bonds in the polycarbonate polyurethane is 3% by mass or more and 20% by mass or less relative to the mass of the polycarbonate polyurethane.
[0024] 2. The highly adhesive polyester film according to item 1 above, wherein the content of the n-hexanediol component in 100 mol % of the diol component in the polycarbonate diol constituting the polycarbonate polyurethane is 5 mol % or more and 30 mol % or less.
[0025] 3. The highly adhesive polyester film according to item 1 or 2 above, wherein the melting point of the polycarbonate diol constituting the polycarbonate polyurethane is 10° C. or higher.
[0026] Effects of the Invention
[0027] According to the present invention, a highly adhesive polyester film having excellent adhesion between a functional layer such as a hard coat layer and an adhesive and a polyester film as a substrate, particularly excellent adhesion after long-term storage and having adhesion reliability can be provided, which can be widely used in optical applications and the like. DETAILED DESCRIPTION
[0028] (Polyester film)
[0029] The polyester film used as the substrate in the present invention is a film mainly composed of a polyester resin. Here, "a film mainly composed of a polyester resin" refers to a film formed by a resin composition containing 50% by mass or more of a polyester resin. When blended with other polymers (such as polycarbonate resins, polyimide resins, etc.), it refers to a film containing 50% by mass or more of a polyester resin, and when copolymerized with other monomers, it refers to a film containing 50 mol% or more of a polyester structural unit. Preferably, the polyester film contains 90% by mass or more of a polyester resin, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0030] The material of the polyester resin is not particularly limited, and a copolymer or a blended resin thereof formed by polycondensation of a dicarboxylic acid component and a diol component can be used. Examples of the dicarboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, diphenyl carboxylic acid, diphenoxyethane dicarboxylic acid, diphenyl sulfone carboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, dodecanedicarboxylic acid, and the like.
[0031] Examples of the diol component constituting the polyester resin include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0032] The dicarboxylic acid component and the diol component constituting the polyester resin may be used alone or in combination of two or more. In addition, other acid components such as trimellitic acid and other hydroxyl components such as trimethylolpropane may be appropriately added.
[0033] As the polyester resin, specifically, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc. can be listed, among which polyethylene terephthalate is preferred for the balance between physical properties and cost. In addition, in order to control optical properties such as polarization, it is also preferred to include other copolymer components and other polymers. From the viewpoint of controlling the optical properties of the polyester film, diethylene glycol, copolymer components having norbornene in the side chain, etc. can be listed as preferred copolymer components.
[0034] In order to improve the handling properties of the polyester film, such as the slipperiness and windability, the film may contain inactive particles, but in order to maintain high transparency, the content of inactive particles in the film is preferably as small as possible. Therefore, it is preferred to have a multilayer structure containing particles only on the surface layer of the film, or to have substantially no particles in the film and only the coating layer laminated on at least one side of the polyester film contain particles.
[0035] It should be noted that the term "substantially free of particles" means, for example, in the case of inorganic particles, that the content of the element derived from the particles is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when the element is quantitatively analyzed by fluorescent X-ray analysis. This is because even if particles are not actively added to the base film, sometimes contaminants derived from foreign matter, raw resins, or contaminants attached to pipes and equipment in the film manufacturing process will be peeled off and inevitably mixed into the film.
[0036] When the polyester film is formed into a multilayer structure, a two-layer structure in which the inner layer contains substantially no inactive particles and only the outermost layer contains inactive particles is preferred because both transparency and processability can be achieved.
[0037] The polyester film as the base material can be a single layer, or it can be stacked with more than two layers. In addition, as long as it is within the scope of the effect of the present invention, various additives can be contained in the film as required. As additives, for example, antioxidants, light fastness agents, anti-gelling agents, organic wetting agents, antistatic agents, ultraviolet light absorbers, surfactants, etc. can be listed. When the film has a stacked structure, it is also preferred to contain additives according to the function of each layer as required. For example, in order to prevent the light degradation of the polarizer, adding ultraviolet light absorbers in the inner layer is also a preferred mode.
[0038] The polyester film can be manufactured according to conventional methods. For example, it can be obtained by the following methods, etc.: the above-mentioned polyester resin is melt-extruded into a film, and it is cooled and solidified on a casting drum to form a film. As the polyester film in the present invention, any one of a non-stretched film and a stretched film can be used, but from the viewpoint of durability such as mechanical strength and chemical resistance, a stretched film is preferably used. In the case where the polyester film is a stretched film, the stretching method is not particularly limited, and longitudinal uniaxial stretching, transverse uniaxial stretching, longitudinal and transverse biaxial stretching in sequence, longitudinal and transverse biaxial stretching, etc. can be used. When stretching the polyester film, the stretching can be implemented before laminating the adhesive coating layer described later, or it can be implemented after laminating the adhesive coating layer. It is also possible to perform uniaxial stretching in the longitudinal or transverse direction in front of the laminated adhesive coating layer, and stretch in another direction after laminating the coating layer.
[0039] (Coating layer)
[0040] The highly adhesive polyester film of the present invention is preferably a polyester film in which a highly adhesive coating layer is laminated on the above-mentioned polyester base film. The coating layer may contain a binder resin and an additive.
[0041] Next, each component of the coating layer will be described in detail.
[0042] As a binder resin constituting the coating layer, a resin having good adhesion is suitable. In the present invention, a polycarbonate polyurethane as a carbamate resin having a polycarbonate structure is suitable for use, and further, it is preferably provided with a structure having a normal hexamethylene chain at the α position of the carbonate bond in the polycarbonate polyurethane. It is believed that this is because it has compatibility with the composition of the functional layer described later, and because the functional layer is formed by a curing reaction based on UV irradiation, and the resin is a carbamate resin having a polycarbonate structure that easily forms free radicals by UV irradiation and maintaining a certain degree of softness and rigidity.
[0043] The polycarbonate polyurethane preferably has a structure having a hexamethylene chain at the α-position of the carbonate bond, and when the polycarbonate polyurethane is set to 100 mass %, the content of the hexamethylene chain is preferably 3 mass % or more and 20 mass % or less, more preferably 5 mass % or more and 18 mass % or less, and particularly preferably 7 mass % or more and 16 mass % or less.
[0044] When the content of the hexamethylene chain at the α position of the carbonate bond is below 20 mass %, the adhesion with the functional layer under high temperature and high humidity can be maintained, so it is preferred. When the content is above 3 mass %, the balance of flexibility and rigidity can be maintained, and the adhesion with the polyester substrate film under normal temperature and high temperature and high humidity can be maintained, so it is preferred.
[0045] The polycarbonate polyurethane is preferably formed by polycarbonate diol and polyisocyanate, and the hexamethylene chain is preferably introduced in the form of the diol component of the polycarbonate diol. In the polycarbonate diol, it is also preferred to include a diol component other than the diol component having the hexamethylene chain. The diol component other than the diol component having the hexamethylene chain is not particularly limited, for example, ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 2,2-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, etc. Among them, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, etc. are also good in operability and suitable for mixing.
[0046] The reason why the effects of the present invention can be exhibited by suppressing the normal hexamethylene chains within a certain range is presumed to be as follows.
[0047] By adjusting the content of the hexamethylene chain at the α position of the carbonate bond to a range of more than 3% by mass and less than 20% by mass, the rigidity of the resin can be maintained and the flexibility of the resin can be improved. It can be seen that in the adhesion with the functional layer as the adherend, not only the initial adhesion can be satisfied, but also the retention of adhesion over time can be improved.
[0048] Specifically, the adhesion to the functional layer provided on the coating layer described later can be improved, and a thin film that maintains its quality over a long period of time can be obtained.
[0049] In the present invention, the crosslinking agent contained in the composition for forming the coating layer is preferably a blocked isocyanate crosslinking agent of hexamethylene diisocyanate. It is believed that by making the content of the normal hexamethylene chain in the polycarbonate polyurethane molecular chain within a specific range, interactions will occur not only between polycarbonate polyurethane molecules but also between the normal hexamethylene chains of hexamethylene diisocyanate as a crosslinking agent, and through this interaction, it is easy to construct an optimal crosslinking network structure in the coating film.
[0050] In the present invention, it is preferred to form a crosslinked structure in the coating layer, and preferably contain a crosslinking agent. Furthermore, the crosslinking agent is preferably a blocked isocyanate crosslinking agent selected from allophanate, biuret or adduct of hexamethylene diisocyanate.
[0051] In addition, by including blocked isocyanate of allophanate, biuret or adduct in the composition, the reactivity is improved, the crosslinking reaction is easy to proceed, the crosslinking density of the obtained coating layer can be increased, and the density of the obtained coating layer can be improved.
[0052] On the other hand, in the case of a cyclic structure such as uretdione or isocyanurate, since the steric hindrance is high as a polymer, it is difficult to achieve interaction with the normal hexamethylene chain derived from the polycarbonate diol constituting the polycarbonate polyurethane, which is not so preferable.
[0053] Specifically, the adhesion of a functional layer such as a hard coat layer or an adhesive applied on the coating layer described later can be improved, and a thin film that maintains adhesion for a long period of time can be obtained.
[0054] In the present invention, the coating layer-forming composition preferably contains a blocked isocyanate crosslinking agent in order to control the reactivity of isocyanate. Examples of the capping agent include bisulfite compounds such as sodium bisulfite, pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole, phenol compounds such as phenol and cresol, aliphatic alcohol compounds such as methanol and ethanol, active methylene compounds such as dimethyl malonate and acetylacetone, thiol compounds such as butyl mercaptan and dodecyl mercaptan, acid amide compounds such as acetanilide and acetamide, lactam compounds such as ε-caprolactam and δ-valerolactam, acid imide compounds such as succinimide and maleic imide, oxime compounds such as acetaldehyde oxime, acetone oxime, and methyl ethyl ketone oxime, and amine compounds such as diphenylaniline, aniline, and ethyleneimine. From the viewpoint of reactivity, the present system is preferably provided with a capping agent having a pyrazole skeleton.
[0055] In addition, from the viewpoint of imparting water dispersibility in an aqueous solvent, it is preferred to introduce a hydrophilic group into the blocked isocyanate crosslinking agent. In addition, as hydrophilicity, it is preferred to introduce anionic groups such as carboxyl or sulfonic acid groups, and nonionic groups such as oxyalkyl groups. These hydrophilic groups can be prepared by reacting a polyisocyanate as the basis of the blocked isocyanate with a compound having a hydrophilic group and reactive groups such as a hydroxyl group in advance.
[0056] In the solid content of all binder resins and crosslinking agents contained in the coating layer forming composition, it is preferred to contain the blocked isocyanate crosslinking agent in an amount of 5% by mass or more and 50% by mass or less. More preferably, it is 10% by mass or more and 45% by mass or less. Further preferably, it is 10% by mass or more and 40% by mass or less, and most preferably, it is 10% by mass or more and 20% by mass or less. If it is 5% by mass or more, the strength of the coating film of the coating layer can be maintained, and the adhesion under high temperature and high humidity is good. If it is 50% by mass or less, the flexibility of the coating layer can be maintained, and the adhesion under normal temperature, high temperature and high humidity can be maintained, so it is preferred.
[0057] When all diol components in the polycarbonate diol constituting the polycarbonate polyurethane are set to 100 mol%, the content of the n-hexanediol component therein is preferably from 5 mol% to 30 mol%, more preferably from 6 mol% to 28 mol%, particularly preferably from 7 mol% to 26 mol%.
[0058] In addition, the melting point of the polycarbonate diol constituting the polycarbonate polyurethane is preferably 10°C or higher, more preferably 20°C or higher, and further preferably 30°C or higher. When the melting point is 10°C or higher, the crystallinity of the prepared polycarbonate polyurethane is improved, the hardness and rigidity are improved, and the mechanical properties as a coating layer are improved. The melting point of the polycarbonate diol is preferably 10°C or higher, and is also preferably 150°C or lower, and is also preferably 100°C or lower.
[0059] The binder resin in the present invention may be polycarbonate polyurethane alone and included in the coating layer forming composition, or may be used in combination with other types of resins to form the coating layer. In this case, polyester resin is suitable in consideration of adhesion to the substrate.
[0060] When the total mass of the binder resin and the crosslinking agent in the coating layer forming composition is set to 100 mass%, from the viewpoint of adhesion, the binder resin preferably accounts for 50 to 95 mass%, more preferably 55 to 90 mass%, further preferably 60 to 90 mass%, and most preferably 80 to 90 mass%. If it is less than 95 mass%, the strength of the coating film of the coating layer can be maintained, and the adhesion under high temperature and high humidity is good. If it is more than 50 mass%, the softness of the coating layer can be maintained, and the adhesion under normal temperature, high temperature and high humidity can be maintained, so it is preferred. The binder resin can be all polycarbonate polyurethane, or other binder resins can be mixed. Polycarbonate polyurethane preferably accounts for more than 10 mass% in the binder resin, and more preferably accounts for more than 20 mass%. When a binder resin such as polyester other than polycarbonate polyurethane is included as a binder resin, it is preferably limited to less than 90 mass%, and more preferably limited to less than 80 mass%. Of course, there may be no binder resin other than polycarbonate polyurethane.
[0061] The coating layer of the highly adhesive polyester film of the present invention is preferably formed from a composition containing a polycarbonate polyurethane satisfying the above conditions and a blocked isocyanate crosslinking agent. As for the expression "formed from the composition", it is difficult to appropriately express the chemical composition of the coating layer formed by curing through a reaction of the crosslinking agent, so such a description is adopted.
[0062] (additive)
[0063] In the coating layer of the present invention, known additives may be added within the range that does not hinder the effect of the present invention, such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc. However, it is preferred not to use environmentally unfriendly substances.
[0064] In the present invention, in order to further improve the anti-blocking property of the coating layer, it is also a preferred method to add particles to the coating layer. In the present invention, as the particles contained in the coating layer, for example, titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, etc. or mixtures thereof, inorganic particles such as calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, etc., and organic polymer particles such as styrene, acrylic acid, melamine, benzoguanamine, silicone, etc. can be listed.
[0065] The average particle size of the particles in the coating layer (the average particle size based on the number of SEM. The same below) is preferably 0.04 to 2.0 μm, and more preferably 0.1 to 1.0 μm. When the average particle size of the particles is 0.04 μm or more, it is easy to form unevenness on the surface of the film, so the operability of the film such as sliding and winding properties is improved, and the processability during bonding is good, so it is preferred. On the other hand, when the average particle size of the particles is 2.0 μm or less, it is not easy for the particles to fall off, so it is preferred. Although there may be no particles in the coating layer, the content of the particles is preferably 1 to 20% by mass relative to the total mass of the resin and the cross-linking agent.
[0066] In the present invention, the thickness of the coating layer is preferably 30 nm or more and 200 nm or less. If it is adjusted within this range, it is easy to achieve both processability and adhesion, which is preferred.
[0067] More preferably, it is 50 nm or more and 150 nm or less, and further preferably 70 nm or more and 100 nm or less. When the thickness of the coating layer is 30 nm or more, the adhesion is good, so it is preferred. When the thickness of the coating layer is 200 nm or less, it is not easy to cause blocking, so it is preferred.
[0068] Regarding the thickness of the coating layer, a cross section of a cut film was observed with a transmission electron microscope (TEM), the thickness of the coating layer was measured at 10 random locations, and the average value was taken as the thickness of the coating layer.
[0069] In the coating layer forming composition, for the purpose of improving the leveling property during coating and the deaeration of the coating solution, a surfactant may also be contained. The surfactant may be any one of a cationic system, an anionic system, a nonionic system, etc., preferably a silicone system, an acetylenic glycol system or a fluorine-based surfactant. These surfactants are preferably included in the coating layer forming composition within the range of the degree of the inhibitory effect and adhesion of the rainbow-like color under the 3 wavelength LED light source.
[0070] As the coating method, either the so-called in-line coating method in which coating is performed simultaneously with the formation of the polyester substrate film or the so-called off-line coating method in which coating is performed separately with a coater after the formation of the polyester substrate film can be applied. However, the in-line coating method is more efficient and is more preferred.
[0071] As a coating method, any known method can be used for coating the coating liquid on the polyethylene terephthalate (hereinafter referred to as PET) film. For example, reverse roll coating, gravure coating, kiss coating, die coating, roller brushing, spray coating, air knife coating, wire rod coating, tubular doctor blade, impregnation coating, curtain coating, etc. can be cited. These methods can be used alone or in combination for coating.
[0072] In the present invention, as a method for providing a coating layer on a polyester film, a method of applying a coating liquid containing a solvent, particles, and a resin on a polyester film and drying the coating liquid can be cited. As a solvent, water or a mixed system of water and an organic solvent can be cited. Preferably, from the viewpoint of environmental issues, water alone or a mixture of water and a water-soluble organic solvent is preferred.
[0073] For example, examples of water-soluble organic solvents include alcohols such as isopropyl alcohol and ethanol, ketones such as methyl ethyl ketone, ethers such as butyl cellosolve, amines such as triethanolamine, and amides such as N-methylpyrrolidone.
[0074] The solid content concentration of the coating liquid varies depending on the type of binder resin, the type of solvent, etc., and is preferably 2% by mass or more, more preferably 4% by mass or more. The solid content concentration of the coating liquid is preferably 35% by mass or less, more preferably 15% by mass or less.
[0075] The drying temperature after coating varies depending on the type of binder resin, the type of solvent, the presence or absence of a crosslinking agent, the solid content concentration, etc., but is preferably 80° C. or higher and 250° C. or lower.
[0076] (Manufacturing of highly adhesive polyester film)
[0077] The polyester film used as the substrate of the highly adhesive polyester film of the present invention can be produced according to a conventional polyester film production method. For example, the following method can be cited: a polyester resin is melted, extruded and formed into a sheet to obtain a non-oriented polyester, the obtained non-oriented polyester is stretched in the longitudinal direction by a roller speed difference at a temperature above the glass transition temperature, and then stretched in the transverse direction by a tenter and subjected to heat treatment.
[0078] The polyester film of the present invention can be a uniaxially stretched film or a biaxially stretched film. However, when a biaxially stretched film is used as a protective film on the front surface of a liquid crystal panel, even if no rainbow-like color spots are observed when observing from directly above the film surface, rainbow-like color spots may sometimes be observed when observing from an oblique direction, so care needs to be taken.
[0079] This phenomenon is due to the fact that the biaxially stretched film is composed of a refractive index ellipsoid with different refractive indices in the traveling direction, the width direction, and the thickness direction, and there is a direction in which the delay amount becomes zero (the refractive index ellipsoid looks like a perfect circle) according to the transmission direction of the light inside the film. Therefore, if the liquid crystal display screen is observed from a specific oblique direction, a point where the delay amount becomes zero is sometimes generated, and a concentric rainbow-shaped color spot is generated with this point as the center. Moreover, if the angle from directly above the film surface (normal direction) to the position where the rainbow-shaped color spot can be observed is set to θ, the larger the birefringence in the film surface, the larger the angle θ, and the more difficult it is to observe the rainbow-shaped color spot. There is a tendency for the angle θ to become smaller in the biaxially stretched film, and therefore, it is preferably a uniaxially stretched film from the viewpoint that the rainbow-shaped color spot is not easily observed. However, from the viewpoint of mechanical properties, it is preferably a biaxially stretched film.
[0080] (Laminated polyester film)
[0081] It is also a preferred mode to provide a functional layer imparting various characteristics on the coating layer of the easy-adhesive polyester film of the present invention. Characteristics refer to the functionality of an anti-glare layer, an anti-glare anti-reflection layer, an anti-reflection layer, a low-reflection layer, and an antistatic layer in addition to the aforementioned hard coating layer for the purpose of anti-reflection, glare suppression, rainbow unevenness suppression, and scratch suppression. The characteristics can use various characteristics known in the technical field, and the types are not particularly limited. Below, each characteristic is described.
[0082] For example, in the formation of hard coat, known hard coat materials can be used, which are not particularly limited, and resin compounds polymerized and / or reacted by drying, heat, chemical reaction, or irradiation of electron beams, radiation, and ultraviolet rays can be used. As such curable resins, curable resins of melamine, acrylic acid, silicone, and polyvinyl alcohol can be listed. From the viewpoint of obtaining high surface hardness or optical design, it is preferably a photocurable acrylic acid curable resin. As such acrylic acid curable resins, multifunctional (methyl) acrylate monomers and acrylic acid oligomers can be used. As examples of acrylic acid oligomers, polyester acrylates, epoxy acrylates, urethane acrylates, polyether acrylates, polybutadiene acrylates, silicone acrylates, etc. can be listed. By mixing reaction diluents, photopolymerization initiators, sensitizers, etc. in these acrylic acid curable resins, it is possible to obtain a coating composition for forming the optical functional layer.
[0083] The hard coat layer may have an anti-glare function (anti-glare function) for scattering external light. The anti-glare function (anti-glare function) may be obtained by forming concavo-convex on the surface of the hard coat layer. At this time, the haze of the film is preferably 0 to 50%, more preferably 0 to 40%, and particularly preferably 0 to 30%. Of course, 0% is ideal, and it may be 0.2% or more, or 0.5% or more.
[0084] In addition, in order to implement low reflection processing (anti-reflection processing) that suppresses light reflection by stacking multiple layers of different refractive indexes and changing the light transmission characteristics, it is preferred to adjust the refractive index of the hard coat layer and other functional layers to achieve a reflectivity of 0 to 1.0%, more preferably 0 to 0.8%, and particularly preferably 0 to 0.5%. Of course, 0% is ideal, and it can be 0.05% or more, or 0.1% or more.
[0085] The easily adhesive polyester film of the present invention can also be used as a polarizer protective film. Usually, polarizer protective films are arranged on both sides of the polarizer to form a polarizing plate, and preferably, the polarizer protective film on at least one side of the polarizer is the easily adhesive polyester film for polarizer protection. The polarizer protective film on the other side can be the easily adhesive polyester film of the present invention, and it is also preferred to use a film without birefringence represented by a cellulose triacetate film, an acrylic film, or a norbornene film.
[0086] As a polarizer, for example, a polarizer containing a dichroic material such as iodine in a polyvinyl alcohol film can be cited. The polarizer protective film is bonded to the polarizer directly or via an adhesive layer, and is preferably bonded via an adhesive from the viewpoint of improving adhesion. At this time, the easy-adhesion layer of the present invention is preferably arranged on the polarizer surface or the adhesive layer surface. As a polarizer preferred for bonding the polyester film of the present invention, for example, a polarizer obtained by dyeing and adsorbing the polyvinyl alcohol film with iodine and a dichroic material, uniaxially stretching in a boric acid aqueous solution, washing and drying while maintaining the stretched state can be cited. The stretching ratio of uniaxial stretching is generally about 4 to 8 times. As a polyvinyl alcohol film, polyvinyl alcohol is suitable, and commercial products such as "KURARAY VINYLON" [manufactured by Kuraray Co., Ltd.], "Tohcello VINYLON" [manufactured by Mitsui Chemicals Tohcello, Inc.], and "Nichigo Vinylon" [manufactured by Nippon Synthetic Chemical Industry Co., Ltd.] can be used. Examples of the dichroic material include iodine, disazo compounds, and polymethine dyes.
[0087] When the adhesive layer is thinned, the adhesive applied to the polarizer is preferably an aqueous adhesive, that is, an adhesive obtained by dissolving or dispersing the adhesive component in water. For example, polyvinyl alcohol resins, polyurethane resins, etc. can be used as main components, and in order to improve adhesion, compositions mixed with isocyanate compounds, epoxy compounds, etc. as needed can be used. The thickness of the adhesive layer is preferably 5 μm or less, more preferably 3 μm or less, and further preferably 1 μm or less.
[0088] When a polyvinyl alcohol resin is used as the main component of the adhesive, in addition to partially saponified polyvinyl alcohol and completely saponified polyvinyl alcohol, a modified polyvinyl alcohol resin such as carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol can be used. The concentration of the polyvinyl alcohol resin in the adhesive is preferably 1 to 10% by mass, more preferably 2 to 7% by mass.
[0089] As an adhesive applied to the polarizer, when you want to further improve productivity, it is preferred to use a photocurable adhesive. The thickness of the adhesive layer after curing can be arbitrarily set according to the characteristic design of the polarizing plate, but from the viewpoint of reducing the cost of adhesive materials, it is preferably small. It is usually 0.01 to 20 μm, preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm. When the thickness of the adhesive layer is 0.01 μm or more, bubbles are not easily mixed into the adhesive layer, and the adhesion and durability are good, so it is preferred. When the adhesive layer is 20 μm or less, the reaction rate of the adhesive is sufficient, and the moisture and heat resistance of the polarizing plate becomes good, so it is preferred.
[0090] The photocurable adhesive preferably contains an epoxy compound containing no aromatic ring as a main component and a photocationic curable component (I) and a photocationic polymerization initiator (II).
[0091] The photocurable adhesive preferably has an epoxy compound that does not contain an aromatic ring as the main component. The epoxy compound that does not contain an aromatic ring is an epoxy compound other than an aromatic epoxy compound, hereinafter referred to as an aliphatic epoxy compound. "Epoxy compound" refers to a compound having at least one epoxy group in the molecule. The aliphatic epoxy compound as the main component may contain two or more epoxy compounds. "Main component" means that the content of the aliphatic epoxy compound is 50% by mass or more in 100% by mass of the photocurable adhesive. The content of the aliphatic epoxy compound is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more.
[0092] The aliphatic epoxy compound may be an epoxy compound having an alicyclic ring, or an epoxy compound not containing an alicyclic ring and consisting only of a linear hydrocarbon structure and / or a branched hydrocarbon structure. In addition, the aliphatic epoxy compound may contain an unsaturated bond such as a double bond, or may further contain a hetero atom (oxygen atom, nitrogen atom, sulfur atom, halogen atom, etc.) other than the oxygen atom contained in the epoxy group.
[0093] Photocationic curing component (I)
[0094] The photocationic curing component (I) is a component that provides adhesive force by polymerization curing based on irradiation with active energy rays, and preferably contains the first epoxy compound (I-1) described in detail below. The photocationic curing component (I) preferably contains the first epoxy compound (I-1) and also contains the second epoxy compound (I-2) or the third epoxy compound (I-3) described in detail below, and more preferably contains the first epoxy compound (I-1) and also contains at least the second epoxy compound (I-2). The photocationic curing component (I) further preferably contains the first epoxy compound (I-1) and also contains the second epoxy compound (I-2) and the third epoxy compound (I-3).
[0095] The photocurable adhesive preferably contains a photocationic polymerization initiator (II). Thus, the photocationic curing component can be cured by cationic polymerization based on irradiation of active energy rays to form an adhesive layer. The photocationic polymerization initiator (II) generates cationic species or Lewis acids by irradiation of active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams, and initiates the polymerization reaction of the photocationic curing component. The photocationic polymerization initiator (II) uses light to generate catalysis, so even if it is mixed with a photocationic curing component, the storage stability and workability are excellent. As compounds that can be used as photocationic polymerization initiators (II) that generate cationic species and Lewis acids by irradiation of active energy rays, for example, aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts and other onium salts; iron-arene complexes, etc.
[0096] Examples of the aromatic diazonium salt include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.
[0097] Examples of the aromatic iodonium salt include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.
[0098] Examples of the aromatic sulfonium salt include triphenylsulfonium hexafluorophosphate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4-bis[diphenylsulfonium]diphenyl sulfide bishexafluorophosphate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide bishexafluoroantimonate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide bishexafluorophosphate, 7-[di(p-methylbenzoyl)sulfonium]-2-isothiazolylsulfonate, Propylthioxanthone hexafluoroantimonate, 7-[di(p-methylbenzoyl)sulfonium]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4-diphenylsulfonium-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4-diphenylsulfonium-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4-di(p-methylbenzoyl)sulfonium-diphenyl sulfide tetrakis(pentafluorophenyl)borate.
[0099] Examples of the iron-arene complex include xylene-cyclopentadienyl iron (II) hexafluoroantimonate, cumene-cyclopentadienyl iron (II) hexafluorophosphate, and xylene-cyclopentadienyl iron (II) tris(trifluoromethylsulfonyl) methide.
[0100] The photocationic polymerization initiator (II) may be used alone or in combination of two or more. Among the above, aromatic sulfonium salts in particular also have ultraviolet absorption properties in the wavelength region near 300 nm, and thus can provide an adhesive layer with excellent curability and good mechanical strength and bonding strength, and are therefore preferably used.
[0101] The content of the photocationic polymerization initiator (II) is preferably 1 to 10 parts by mass, more preferably 2 to 6 parts by mass, relative to 100 parts by mass of the photocationic curing component as a whole. By containing more than 1 part by mass of the photocationic polymerization initiator (II), the photocationic curing component can be fully cured, and high mechanical strength and bonding strength can be provided to the obtained polarizing plate. On the other hand, when its content increases, the ionic substance in the cured product increases, so that the hygroscopicity of the cured product increases, and there is a possibility of reducing the durability of the polarizing plate, so the content of the photocationic polymerization initiator (II) is preferably less than 10 parts by mass relative to 100 parts by mass of the photocationic curing component.
[0102] The uses of the laminated polyester film obtained by imparting a functional layer to the coating layer of the easily adhesive polyester film of the present invention mainly cover all optical films, and are particularly suitable for use as base films for optical components such as LCDs, flat-panel TVs, CRTs, etc., such as prism lens sheets, AR (anti-reflection) films, hard coating films, diffuser plates, and anti-shatter films, near-infrared absorption filters as components of front panels for plasma displays, touch panels, transparent conductive films for electroluminescence, etc.
[0103] The electron beam or ultraviolet-cured acrylic resin used to form the functional layer is, in detail, a resin having an acrylate or methacrylate functional group. For example, a resin containing a relatively low molecular weight polyester resin, a polyether resin, an acrylic resin, an epoxy resin, a urethane resin, an alkyd resin, a spiroacetal resin, a polybutadiene resin, a polythiol polyene resin, a (meth)acrylate of a multifunctional compound such as a polyol, an oligomer or a prepolymer, and a monofunctional monomer such as ethyl (meth)acrylate and ethylhexyl (meth)acrylate as a reactive diluent, and a multifunctional monomer such as trimethylolpropane tri(meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, etc. can be used.
[0104] Moreover, in the case of electron beam or ultraviolet curable resins, acetophenones, benzophenones, Michaelis benzoylbenzoate, α-amyloxime ester, tetramethylthiuram monosulfide, and thioxanthones can be mixed with the above-mentioned resin as photopolymerization initiators, and n-butylamine, triethylamine, tri-n-butylphosphine, etc. can be mixed with the above-mentioned resin as photosensitizers.
[0105] In addition, organosilicon-based (siloxane-based) thermosetting resins can be produced by hydrolyzing and condensing organosilicon compounds alone or by mixing two or more of them under an acid or base catalyst. In particular, in the case of low reflection, it is more appropriate to mix one or more fluorosilane compounds and perform hydrolysis and condensation reactions in order to improve low refractive index and pollution resistance.
[0106] (Manufacture of laminated polyester film)
[0107] The method for producing a functional polyester film using the highly adhesive polyester film of the present invention will be described, but the invention is not limited to the specific example described.
[0108] The electron beam or ultraviolet curable acrylic resin, oligomer, monomer or silicone thermosetting resin is preferably applied on the coating layer of the aforementioned easy-adhesive polyester film. In the case where coating layers are provided on both sides, the coating is applied on at least one coating layer. The coating liquid does not need to be diluted in particular, but it is not a big problem to dilute it with an organic solvent according to the viscosity, wettability, coating thickness and the like of the coating liquid. The coating layer is formed by applying the coating liquid on the aforementioned film, drying it as needed, and then curing the coating layer by electron beam or ultraviolet irradiation and heating in accordance with the curing conditions of the coating liquid to form a functional layer.
[0109] In the present invention, the thickness of the functional layer is preferably 1 to 15 μm. When the thickness of the functional layer is 1 μm or more, the effect of the functional layer on chemical resistance, scratch resistance, antifouling, etc. can be effectively exerted, so it is preferred. On the other hand, when the thickness is 15 μm or less, the flexibility of the functional layer can be maintained, and there is no risk of cracking, etc., so it is preferred.
[0110] As for the scratch resistance, when the coated surface is abraded with black backing paper, it is preferred that the scratches are not noticeable visually. If the scratches are not noticeable in the above evaluation, it is not easy to be scratched when passing through the guide roll, which is preferred from the viewpoint of operability.
[0111] The easily adhesive polyester film and laminated polyester film of the present invention are mainly used for optical purposes, and therefore preferably have high transparency. The lower limit of the haze is ideally 0%, and the closer to 0%, the more preferred. The upper limit of the haze is preferably 2%, and when it is 2% or less, the light transmittance is good, and a clear image can be obtained in a liquid crystal display device, so it is preferred. The haze of the polyester film can be measured, for example, according to the method described below.
[0112] On the coating layer of the adhesive polyester film, a coating liquid for forming a functional layer having the above-mentioned composition can be used. For example, in the case of a hard coat layer, a wire bar or the like is appropriately used for coating, and then dried at 70° C. for 1 minute to remove the solvent. Next, the film coated with the functional layer is irradiated with, for example, a high-pressure mercury lamp at 300 mJ / cm 2 By irradiating with ultraviolet rays, a laminated polyester film having a functional layer can be obtained.
[0113] The adhesion of the coating layer with easy adhesion to the functional layer can be obtained by evaluation based on the measurement method described later. Regarding the adhesion (X) after film formation, it is preferably 95% or more. More preferably, it is 98% or more, and further preferably 100%. When it is 95% or more, it can be said that the adhesion of the coating layer and the functional layer is fully maintained. It should be noted that in the present invention, "after film formation" means that it is continuously stored under a temperature environment below 40°C, which means within 6 months from film formation.
[0114] Regarding the adhesion (Y) of the coating layer with easy adhesion and the functional layer under the high temperature and high humidity conditions of 80°C and 95%RH evaluated by the method described later, as described above, the adhesion is preferably 95% or more. More preferably, it is 98% or more, and further preferably, it is 100%. When it is 95% or more, the adhesion of the coating layer with easy adhesion and the functional layer under the high temperature and high humidity conditions can be basically satisfied, and the passability in the post-processing process can be basically satisfied.
[0115] Originally, it would be ideal if the adhesion of the easily adhesive polyester film could be evaluated after being placed in a normal room temperature environment for several weeks to several months. However, since it is difficult to measure the adhesion by placing it in a high temperature and high humidity environment of 80°C and 90% RH for 24 hours as an alternative method in this application.
[0116] The highly adhesive polyester film of the present invention is a film with high adhesion reliability (characteristic of maintaining adhesion even after being placed in a high temperature and high humidity environment), and exhibits high adhesion as an effect even after being exposed to a high temperature and high humidity environment. Therefore, the above X (%) and Y (%) satisfy the following formula (1).
[0117] XY(%)≤5···Formula (1)
[0118] The value of formula (1) is preferably 5% or less, more preferably 3% or less, and further preferably 0%. When it is 5% or less, it can be judged that there is no significant difference in the adhesion after film formation and the adhesion after wet heat treatment, and both can be judged to be sufficiently adhered.
[0119] Therefore, it can be seen that even if the film is stored for a long period of time, the adhesiveness of the functional layer is not reduced, and the adhesiveness reliability can be ensured.
[0120] Example
[0121] Next, the present invention will be described in detail using Examples, Comparative Examples, and Reference Examples, but the present invention is not limited to the following Examples. In addition, the evaluation method used in the present invention is as follows.
[0122] (1) Average particle size
[0123] [Measurement method based on scanning electron microscope]
[0124] The average particle size of the particles can be measured by the following method. The particles are photographed with a scanning electron microscope (SEM), and the maximum particle size (the distance between the two points farthest apart) of 300 to 500 particles is measured at a magnification of 2 to 5 mm for the size of the smallest particle, and the average value is taken as the average particle size. The average particle size of the particles present in the coating layer of the present invention can be measured by this measurement method.
[0125] 〔Dynamic light scattering method〕
[0126] The average particle size of the particles can also be obtained by dynamic light scattering when manufacturing particles and films. The sol is diluted with a dispersion medium, and the parameters of the dispersion medium are used to measure the average particle size using a submicron particle analyzer N4PLUS (manufactured by Beckman Coulter). The average particle size is calculated by the accumulation method. In the dynamic light scattering method, the average particle size of the particles in the sol is observed, and when there is aggregation between particles, the average particle size of these aggregated particles is observed.
[0127] (2) Haze of highly adhesive polyester film for optical applications
[0128] The haze of the highly adhesive polyester film was measured using a turbidity meter (NDH2000 manufactured by Nippon Denshoku Industries, Ltd.) in accordance with JIS K 7136:2000.
[0129] (3) Adhesion of functional layer (1)
[0130] A hard coat layer was formed on the adhesive coating layer of the polyester film obtained in Examples. The adhesion between the hard coat layer and the base film was determined for the adhesive polyester film having the hard coat layer formed thereon in accordance with 8.5.1 of JIS-K5400-1990.
[0131] The coating liquid used for forming the hard coat layer was prepared as follows.
[0132] (Preparation of coating liquid L for forming hard coat layer)
[0133]
[0134] (BS577 manufactured by Arakawa Chemical Industries, Ltd.)
[0135] Surfactant 0.10 mass%
[0136] Photopolymerization initiator 2.00 mass%
[0137] (Omnirad184 manufactured by IGM Resins BV)
[0138] (Preparation of coating solution M for forming hard coat layer)
[0139] Methyl ethyl ketone 64.40 mass%
[0140] Dipentaerythritol hexaacrylate 27.20 mass%
[0141] (A-DPH manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)
[0142] Polyethylene glycol diacrylate 3.40 mass%
[0143] (LIGHT ACRYLATE 9EG-A manufactured by Kyoeisha Chemical Co., Ltd.)
[0144] Bisphenol A diacrylate 4.00 mass%
[0145] (LIGHT ACRYLATE BP-4PA manufactured by Kyoeisha Chemical Co., Ltd.)
[0146] Photopolymerization initiator 1.00 mass%
[0147] (Omnirad184 manufactured by IGM Resins BV)
[0148] (Formation of hard coat layer)
[0149] The adhesive polyester film prepared in the examples described below was stored at 20°C and 65% RH. After 12 hours from the preparation of the film, the coating solution for forming a hard coat layer of the above composition was applied to the adhesive coating layer using a #14 wire rod and dried at 70°C for 1 minute to remove the solvent. Then, the film coated with the hard coat layer was irradiated with a high-pressure mercury lamp at 300 mJ / cm 2 The ultraviolet rays were irradiated to obtain a hard coating film having a hard coating layer with a thickness of 7 μm.
[0150] The specific method for measuring the adhesion is as follows. A tool guide with a gap interval of 2mm is used to penetrate the hard coating layer, and 100 grid-like scratches reaching the substrate film are given to the hard coating layer surface. Next, a transparent adhesive tape (Nichiban, No. 405; 24mm wide) is adhered to the grid-like scratched surface and wiped with an eraser to make it completely adhered. After that, the transparent adhesive tape is vertically peeled off from the hard coating layer surface of the aforementioned easy-adhesive polyester film with a hard coating layer formed thereon, and the number of grids peeled off from the hard coating layer surface of the easy-adhesive polyester film with a hard coating layer formed thereon is visually counted, and the adhesion of the hard coating layer to the substrate film is calculated by the following formula. It should be noted that those partially peeled off in the grid are also counted as peeled grids.
[0151] Adhesion (%) = {1-(number of peeled meshes / 100)}×100
[0152] (4) Adhesion of functional layer (2)
[0153] A photocurable adhesive layer was formed on the adhesive coating layer of the adhesive polyester film obtained in Examples. The adhesion between the photocurable adhesive layer and the base film was determined according to 8.5.1 of JIS-K5400-1990.
[0154] The coating liquid used for forming the photocurable adhesive layer was prepared as follows.
[0155] (Preparation of coating liquid N for forming photocurable adhesive layer)
[0156] 3,4-Epoxycyclohexylmethyl-3,4'-epoxycyclohexanecarboxylate 23.81 mass%
[0157] (Celloxide2021P manufactured by Daicel Co., Ltd.)
[0158] 1,4-cyclohexanedimethanol diglycidyl ether 23.81 mass%
[0159] (EX-216L manufactured by Nagase Chemtex Corporation)
[0160] 3-Methyl-3-[(3-ethyloxetane-3-yl)methoxymethyl]oxetane
[0161] 47.62% by mass
[0162] (ARON OXETANE DOX221 manufactured by Toa Gosei Co., Ltd.)
[0163] Cationic initiator 4.76 mass%
[0164] (CPI-100P manufactured by Sanapro)
[0165] The aromatic component in all the resins in the prepared photocurable adhesive layer-forming coating liquid N was 13.3% by molar ratio.
[0166] (Formation of Photocurable Adhesive Layer)
[0167] The highly adhesive polyester film prepared in the examples described below was stored at 20°C and 65% RH. After 12 hours from the preparation of the film, the coating liquid for forming the photocurable adhesive layer of the above composition was applied to the highly adhesive coating layer using a #3 wire rod. Then, the film coated with the photocurable adhesive layer was irradiated with a high-pressure mercury lamp at 500 mJ / cm 2 The ultraviolet rays were irradiated to obtain a laminated film for polarizing plate protective film having a photocurable adhesive layer with a thickness of 5 μm.
[0168] (Adhesion Evaluation Method)
[0169] The specific method for measuring the adhesion is as follows. A tool guide with a gap interval of 2 mm is used to penetrate the photocurable adhesive layer, and 100 grid-like scratches reaching the substrate film are given to the photocurable adhesive layer. Next, a transparent adhesive tape (Nichiban, No. 405; 24 mm wide) is adhered to the grid-like scratched surface and wiped with an eraser to make it completely adhered. After that, the transparent adhesive tape is vertically peeled off from the photocurable adhesive layer of the easy-bonding polyester film formed with the photocurable adhesive layer, and the number of grids peeled off from the photocurable adhesive layer of the easy-bonding polyester film formed with the photocurable adhesive layer is visually counted, and the adhesion between the photocurable adhesive layer and the substrate film is calculated by the following formula. It should be noted that the partially peeled grids are also counted as peeled grids.
[0170] Adhesion (%) = {1-(number of peeled meshes / 100)}×100
[0171] (5) Moisture and heat resistance (adhesion after standing at 80°C and 90% RH)
[0172] The obtained highly adhesive polyester film was placed in a high temperature and high humidity chamber at 80°C and 90% RH for 24 hours and then at room temperature (20°C and 65% RH) for 12 hours. Thereafter, a functional layer was formed in the same manner as above and the adhesion to the base film was determined.
[0173] (6) Number average molecular weight
[0174] 0.03 g of the resin was dissolved in 10 ml of tetrahydrofuran, and the number average molecular weight was measured using a GPC-LALLS apparatus, a low angle light scattering photometer LS-8000 (manufactured by Tosoh Corporation, tetrahydrofuran solvent, reference: polystyrene), at a column temperature of 30° C. and a flow rate of 1 ml / min using a column (Showa Denko KF-802, 804, 806).
[0175] (7) Cross-sectional observation using a transmission electron microscope (thickness of coating layer)
[0176] The obtained easy-adhesive polyester film was cut into 1 mm × 10 mm, embedded in epoxy resin, and then thin sections parallel to the short sides of the embedded sample slice were made with an ultrathin slicer. Then, the film obtained by staining the sliced film with ruthenium tetroxide without obvious damage was observed with a transmission electron microscope (JEM2100 manufactured by JEOL Ltd.) at an accelerating voltage of 200 kV and 20,000 times. The thickness of the coating layer at 10 points of each level was measured from the image of the observed coating layer, and the average value was taken as the thickness of the coating layer.
[0177] (8) Content of hexamethylene chains at the α position of carbonate bonds
[0178] The content of the hexamethylene chain was calculated using the following (Formula 2).
[0179] Hexamethylene chain content (mass %) = (mass of hexamethylene chain (g) / mass of polycarbonate polyurethane (g)) × 100 (Formula 2)
[0180] The mass of hexamethylene chains present in the polycarbonate diol was calculated and divided by the mass of the polycarbonate polyurethane prepared.
[0181] (9) Melting point of polycarbonate diol
[0182] Using a differential scanning calorimeter (DSC) DSC-220 manufactured by Seiko Instruments Inc., 5 mg of the sample was sealed in an aluminum press-capped container and the temperature was increased from -100°C to 250°C at a heating rate of 20°C / min. The maximum peak temperature of the heat of fusion was determined as the crystalline melting point.
[0183] Synthesis of polyurethane resin (PU-1)
[0184] In a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 48°C and a number average molecular weight of 1000, 7 parts by mass of dimethylol propionic acid and 200 parts by mass of methyl ethyl ketone as a solvent were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and the infrared spectrum of the reaction liquid was measured to confirm the disappearance of the isocyanate group in the reaction liquid. Then, after the solution was cooled to room temperature, 8.2 parts by mass of triethylamine was added to obtain a polyurethane resin (PU-1) solution with a solid content of 50.0% by mass. The content of the hexamethylene chain present at the α position of the carbonate bond of the polyurethane resin (PU-1) was 38.09% by mass.
[0185] Preparation of polyurethane resin (PU-1) aqueous dispersion (PU-1WD)
[0186] In a reaction vessel equipped with a high-speed stirring homogenizer, add a specified amount of water, adjust the temperature to 25°C, and stir for 2000 min. -1 The mixture was stirred and mixed while slowly adding the aforementioned polyurethane resin (PU-1) solution to disperse the mixture in water. Then, methyl ethyl ketone as a solvent was removed under reduced pressure. The concentration was adjusted with water to prepare a polyurethane resin (PU-1) aqueous dispersion (PU-1WD) having a solid content of 35.0% by mass.
[0187] Synthesis of polyurethane resin (PU-2)
[0188] In a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 40°C and a number average molecular weight of 1000 with 1,4-butanediol as the main raw material, 7 parts by mass of dimethylol propionic acid and 200 parts by mass of methyl ethyl ketone as a solvent were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and the infrared spectrum of the reaction liquid was measured to confirm the disappearance of the isocyanate group in the reaction liquid. Then, after the solution was cooled to room temperature, 8.2 parts by mass of triethylamine was added to obtain a polyurethane resin (PU-2) solution with a solid content of 50.0% by mass. The content of the hexamethylene chain present at the α position of the carbonate bond of the polyurethane resin (PU-2) was 0.00% by mass.
[0189] Preparation of polyurethane resin (PU-2) aqueous dispersion (PU-2WD)
[0190] In a reaction vessel equipped with a high-speed stirring homogenizer, add a specified amount of water, adjust the temperature to 25°C, and stir for 2000 min. -1 The mixture was stirred and mixed while slowly adding the aforementioned polyurethane resin (PU-2) solution to disperse the mixture in water. Then, methyl ethyl ketone as a solvent was removed under reduced pressure. The concentration was adjusted with water to prepare a polyurethane resin (PU-2) aqueous dispersion (PU-2WD) having a solid content of 35.0% by mass.
[0191] Synthesis of polyurethane resin (PU-3)
[0192] In a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 31.8 parts by mass of polycarbonate diol with a number average molecular weight of 1000 and 31.8 parts by mass of polycarbonate diol with a number average molecular weight of 1000 and 1,6-hexanediol as the main raw material, 7 parts by mass of dimethylol propionic acid and 200 parts by mass of methyl ethyl ketone as a solvent were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and the infrared spectrum of the reaction liquid was measured to confirm the disappearance of the isocyanate group in the reaction liquid. Then, after the solution was cooled to room temperature, 8.2 parts by mass of triethylamine was added to obtain a polyurethane resin (PU-2) solution with a solid content of 50.0% by mass. The content of the hexamethylene chain present at the α position of the carbonate bond of the polyurethane resin (PU-2) was 19.05% by mass.
[0193] Preparation of polyurethane resin (PU-3) aqueous dispersion (PU-3WD)
[0194] In a reaction vessel equipped with a high-speed stirring homogenizer, add a specified amount of water, adjust the temperature to 25°C, and stir for 2000 min. -1 The mixture was stirred and mixed while slowly adding the aforementioned polyurethane resin (PU-3) solution to disperse in water. Then, methyl ethyl ketone as a solvent was removed under reduced pressure. The concentration was adjusted with water to prepare a polyurethane resin (PU-3) aqueous dispersion (PU-3WD) having a solid content of 35.0% by mass.
[0195] Synthesis of polyurethane resin (PU-4)
[0196] In a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 33°C and a number average molecular weight of 1000, 7 parts by mass of dimethylol propionic acid and 200 parts by mass of methyl ethyl ketone as a solvent were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and the infrared spectrum of the reaction liquid was measured to confirm the disappearance of the isocyanate group in the reaction liquid. Then, after the solution was cooled to room temperature, 8.2 parts by mass of triethylamine was added to obtain a polyurethane resin (PU-4) solution with a solid content of 50.0% by mass. The content of the hexamethylene chain present at the α position of the carbonate bond of the polyurethane resin (PU-4) was 9.02% by mass.
[0197] Preparation of polyurethane resin (PU-4) aqueous dispersion (PU-4WD)
[0198] In a reaction vessel equipped with a high-speed stirring homogenizer, add a specified amount of water, adjust the temperature to 25°C, and stir for 2000 min. -1 The mixture was stirred and mixed, and the polyurethane resin (PU-4) solution was gradually added to disperse the mixture in water. Then, the methyl ethyl ketone as the solvent was removed under reduced pressure. The concentration was adjusted with water to prepare a polyurethane resin (PU-4) aqueous dispersion (PU-4WD) having a solid content of 35.0% by mass.
[0199] Synthesis of polyurethane resin (PU-5) and preparation of water dispersion (PU-5WD)
[0200] (PU-5) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,4-butanediol / 1,6-hexanediol (=90 / 10 (molar ratio)), and an aqueous dispersion (PU-5WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain, etc., is as described in Table 1.
[0201] Synthesis of polyurethane resin (PU-6) and preparation of water dispersion (PU-6WD)
[0202] (PU-6) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,4-butanediol / 1,6-hexanediol (=70 / 30 (molar ratio)), and an aqueous dispersion (PU-6WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain, etc., is as described in Table 1.
[0203] Synthesis of polyurethane resin (PU-7) and preparation of water dispersion (PU-7WD)
[0204] (PU-7) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,5-pentanediol / 1,6-hexanediol (=80 / 20 (molar ratio)), and an aqueous dispersion (PU-7WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain, etc., is as described in Table 1.
[0205] Synthesis of polyurethane resin (PU-8) and preparation of water dispersion (PU-8WD)
[0206] (PU-8) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,4-cyclohexanedimethanol / 1,6-hexanediol (=75 / 25 (molar ratio)), and an aqueous dispersion (PU-8WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain and the like are as described in Table 1.
[0207] Synthesis of polyurethane resin (PU-9) and preparation of water dispersion (PU-9WD)
[0208] (PU-9) was prepared in the same manner as the synthesis of (PU-4) above, and an aqueous dispersion (PU-9WD) was obtained in the same manner as the preparation of (PU-4WD), except that cyclohexane-1,2-diylbis(methylene)diisocyanate was used instead of dicyclohexylmethane-4,4'-diisocyanate and the molar number was matched. The content of the n-hexamethylene chain was as described in Table 1.
[0209] Synthesis of polyurethane resin (PU-10) and preparation of water dispersion (PU-10WD)
[0210] (PU-10) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,4-butanediol / 1,6-hexanediol (=25 / 75 (molar ratio)), and an aqueous dispersion (PU-10WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain, etc., is as described in Table 1.
[0211] Synthesis of polyurethane resin (PU-11) and preparation of water dispersion (PU-11WD)
[0212] (PU-11) was prepared in the same manner as the synthesis of (PU-4) except that the main raw material of the polycarbonate diol was changed to 1,5-pentanediol / 1,6-hexanediol (=44 / 56 (molar ratio)), and an aqueous dispersion (PU-11WD) was obtained in the same manner as the preparation of (PU-4WD). The content of the n-hexamethylene chain, etc., is as described in Table 1.
[0213] Polymerization of polyester resins (PEs)
[0214] In a stainless steel autoclave equipped with a stirrer, a thermometer and a partial reflux condenser, 342.0 parts by mass of dimethyl 2,6-naphthalate, 35.0 parts by mass of dimethyl terephthalate, 35.5 parts by mass of dimethyl isophthalate-5-sodium sulfonate, 198.6 parts by mass of ethylene glycol, 118.2 parts by mass of 1,6-hexanediol and 0.4 parts by mass of tetra-n-butyl titanate were added, and an ester exchange reaction was carried out at a temperature of 160°C to 220°C for 4 hours. Furthermore, 60.7 parts by mass of sebacic acid were added to carry out an esterification reaction. Then, the temperature was raised to 255°C, and after the reaction system was slowly depressurized, the reaction was carried out under a reduced pressure of 30 Pa for 1 hour and 30 minutes to obtain a copolyester resin (PEs). The obtained copolyester resin (PEs) was light yellow and transparent. The reduced viscosity of the copolyester resin (PEs) was measured, and the result was 0.72dl / g. The glass transition temperature based on DSC was 40°C, and the number average molecular weight was 20,000.
[0215] Preparation of Polyester Water Dispersion (PEsWD)
[0216] 30 parts by mass of copolyester resin (PEs) and 15 parts by mass of ethylene glycol n-butyl ether were placed in a reactor equipped with a stirrer, a thermometer and a reflux device, and heated and stirred at 110°C to dissolve the resin. After the resin was completely dissolved, 55 parts by mass of water were slowly added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to prepare a milky white polyester resin (PEs) water dispersion (PEsWD) with a solid content of 25.0% by mass.
[0217] Preparation of aqueous dispersion (C-1WD) of blocked isocyanate crosslinking agent (C-1)
[0218] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 125.2 parts by mass of a polyisocyanate compound having a biuret structure (Duranate 24A-100 manufactured by Asahi Kasei Chemicals Co., Ltd., NCO concentration 23.1%), 50.0 parts by mass of dipropylene glycol dimethyl ether, and 68.8 parts by mass of 3,5-dimethylpyrazole were added, and stirred at 70°C for 2 hours under a nitrogen atmosphere. Then, the infrared spectrum of the reaction solution was measured to confirm that the absorption of the isocyanate group had disappeared. Next, after cooling to room temperature, 6 parts by mass of polyethylene glycol (n=12) monolaurate were added, and the mixture was stirred at 2000 min. -1 Water was added while stirring and mixing, and the concentration was adjusted with water to prepare an aqueous dispersion (C-1WD) of a blocked isocyanate crosslinking agent (C-1) having a solid content of 30.0% by mass.
[0219] Preparation of aqueous dispersion (C-2WD) of blocked isocyanate crosslinking agent (C-2)
[0220] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 125.2 parts by mass of a polyisocyanate compound having an addition structure (Duranate P301-75E, manufactured by Asahi Kasei Chemicals, Inc., dissolved in ethyl acetate, solid content concentration 75.0%, NCO concentration 12.5%), 50.0 parts by mass of dipropylene glycol dimethyl ether, and 37.2 parts by mass of 3,5-dimethylpyrazole were added, and the mixture was stirred at 70°C for 2 hours under a nitrogen atmosphere. Then, the infrared spectrum of the reaction solution was measured to confirm that the absorption of the isocyanate group had disappeared. Next, after cooling to room temperature, 6 parts by mass of polyethylene glycol (n=12) monolaurate was added, and the mixture was stirred at 2000 min. -1 Water was added while stirring and mixing. After adding water, the ethyl acetate component was removed by reduced pressure distillation, and the concentration was adjusted with water to prepare an aqueous dispersion (C-2WD) of a blocked isocyanate crosslinking agent (C-2) having a solid content of 30.0% by mass.
[0221] Preparation of aqueous dispersion (C-3WD) of blocked isocyanate crosslinking agent (C-3)
[0222] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 125.2 parts by mass of a polyisocyanate compound having an allophanate structure (Duranate A201H manufactured by Asahi Kasei Chemicals Co., Ltd., NCO concentration 17.2%), 50.0 parts by mass of dipropylene glycol dimethyl ether, and 51.2 parts by mass of 3,5-dimethylpyrazole were added, and stirred at 70°C for 2 hours under a nitrogen atmosphere. Then, the infrared spectrum of the reaction solution was measured to confirm that the absorption of the isocyanate group had disappeared. Next, after cooling to room temperature, 6 parts by mass of polyethylene glycol (n=12) monolaurate were added, and the mixture was stirred at 2000 min. -1 Water was added while stirring and mixing, and the concentration was adjusted with water to prepare an aqueous dispersion (C-3WD) of a blocked isocyanate crosslinking agent (C-3) having a solid content of 30.0% by mass.
[0223] Preparation of aqueous dispersion (C-4WD) of blocked isocyanate crosslinking agent (C-4)
[0224] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 35.00 parts by mass of 3,5-dimethylpyrazole were added dropwise to 100 parts by mass of a polyisocyanate compound having an isocyanurate structure prepared from 1,6-hexamethylene diisocyanate by a conventional method (Duranate TPA-100 manufactured by Asahi Kasei Chemicals Co., Ltd., NCO concentration 23.1%) and 17.5 parts by mass of N-methylpyrrolidone, and the mixture was kept at 70°C for 1 hour under a nitrogen atmosphere. Then, 12.50 parts by mass of dimethylol propionic acid were added dropwise. The infrared spectrum of the reaction solution was measured, and after confirming that the absorption of the isocyanate group had disappeared, 8.72 parts by mass of N,N-dimethylethanolamine was added. In this state, the mixture was stirred for 1 hour, and then an appropriate amount of water was added to obtain an aqueous dispersion (C-4WD) of a blocked isocyanate crosslinking agent (C-4) having a solid content of 40.0% by mass.
[0225] Preparation of aqueous dispersion (C-5WD) of blocked isocyanate crosslinking agent (C-5)
[0226] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 27.0 parts by mass of 3,5-dimethylpyrazole were added dropwise to 100 parts by mass of a polyisocyanate compound having a biuret structure (NCO concentration 17.7%) prepared from isophorone diisocyanate by a conventional method and 17.5 parts by mass of N-methylpyrrolidone, and the mixture was kept at 70°C for 1 hour under a nitrogen atmosphere. Then, 9.5 parts by mass of dimethylol propionic acid were added dropwise. After the infrared spectrum of the reaction solution was measured and it was confirmed that the absorption of the isocyanate group had disappeared, 6.6 parts by mass of N,N-dimethylethanolamine was added. In this state, after stirring for 1 hour, an appropriate amount of water was added to obtain an aqueous dispersion (C-5WD) of a blocked isocyanate crosslinking agent (C-5) having a solid content of 30.0% by mass.
[0227] (Example 1)
[0228] (Adjustment of coating liquid)
[0229] A coating liquid having the following composition was prepared.
[0230] Water 45.18 parts by mass
[0231] Isopropyl alcohol 30.57 parts by mass Silica sol 4.15 parts by mass
[0232] (Silica sol with an average particle size of 100 nm and a solid content concentration of 10.5% by mass)
[0233] PU-3WD 10.83 parts by mass (solid content concentration 35.0% by mass)
[0234] C-1WD 8.43 parts by mass (solid content concentration 30.0% by mass)
[0235] Surfactant 0.50 parts by mass (silicone-based, solid content concentration 10.0% by mass)
[0236] 0.34 parts by mass of high boiling point solvent (production of highly adhesive polyester film)
[0237] As a film base polymer, PET resin pellets having an intrinsic viscosity (solvent: phenol / tetrachloroethane = 60 / 40) of 0.62 dl / g and substantially free of particles were dried at 135° C. for 6 hours under a reduced pressure of 133 Pa. Thereafter, the pellets were supplied to an extruder, melt-extruded at about 280° C. into a sheet, and rapidly cooled and solidified on a rotating cooling metal roll whose surface temperature was maintained at 20° C. to obtain an unstretched PET sheet.
[0238] Next, the coating solution was applied to one side of the PET film by roll coating and dried at 80°C to a coating weight of 0.12 g / m2 after final stretching. 2Then, the film was stretched to 4.0 times in the width direction at 150°C in a tenter, heated at 230°C while the length of the film in the width direction was fixed, and further relaxed in the width direction at 230°C to obtain an easily adhesive polyester film having a thickness of 50 μm.
[0239] The thickness of the highly adhesive coating layer of the obtained highly adhesive polyester film was 82 nm, and the haze of the film was 0.54%.
[0240] Next, the hard coat layer-forming coating liquid L is applied on the adhesive coating layer of the adhesive polyester film according to the above-mentioned formation method to obtain a laminated polyester film.
[0241] The adhesion of the hard coat layer of the obtained laminated polyester film was evaluated. As a result, the adhesion X was 100%.
[0242] Furthermore, the obtained highly adhesive polyester film was placed in a high temperature and high humidity tank at 80°C and 90 RH% for 24 hours, and then placed at room temperature for 12 hours. Thereafter, a hard coating layer was formed on the highly adhesive coating layer of the treated highly adhesive polyester film using a coating liquid L for forming a hard coating layer, thereby obtaining a laminated polyester film.
[0243] The adhesion of the hard coat layer of the obtained laminated polyester film was evaluated. As a result, the adhesion Y was 100%.
[0244] From this result, XY=5(%). These results are shown in Table 1.
[0245] The roll was left to stand in an environment of temperature: 0°C to 30°C and humidity: 10%RH to 80%RH for 6 months, and a sample was collected from the product roll, and the adhesion was evaluated in the same manner as above.
[0246] The results of the adhesion evaluation of the rolls actually stored are recorded in Table 1 as Z. Regarding the adhesion reliability based on the results, the case where 100% or more adhesion can be guaranteed is evaluated as ◎, the case where 95% or more and 100% or less adhesion can be guaranteed is evaluated as 0 to ◎, the case where 95% or more adhesion can be guaranteed is evaluated as 0, and the case where 95% or more adhesion cannot be guaranteed is evaluated as ×. The evaluation results of the adhesion reliability are recorded in the column of the adhesion reliability of Table 1. The case where 95% or more adhesion can be guaranteed can confirm that the adhesion reliability can be guaranteed.
[0247] The evaluation results are as follows: the adhesion (Z) is 95%, and as a result, the adhesion reliability is 0, and it is judged that the adhesion reliability can be guaranteed.
[0248] (Example 2)
[0249] A highly adhesive polyester film was obtained in the same manner as in Example 1 except that the resin used was changed to PU-4WD and a coating liquid prepared as follows was used.
[0250] Water 45.18 parts by mass
[0251] Isopropyl alcohol 30.57 parts by mass Silica sol 4.15 parts by mass (silica sol with an average particle size of 100 nm, solid content concentration of 10.5% by mass)
[0252] PU-4WD 10.83 parts by mass (solid content concentration 35.0% by mass)
[0253] C-1WD 8.43 parts by mass (solid content concentration 30.0% by mass)
[0254] Surfactant 0.50 parts by mass (silicone-based, solid content concentration 10.0% by mass)
[0255] High boiling point solvent 0.34 parts by mass
[0256] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0257] (Examples 3 and 4)
[0258] Except having changed the thickness of the coating liquid into the thickness described in Table 1, it carried out similarly to Example 1, and obtained the highly adhesive polyester film.
[0259] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0260] (Example 5)
[0261] A highly adhesive polyester film was obtained in the same manner as in Example 1 except that a coating liquid having the following composition was prepared.
[0262] Water 44.10 parts by mass
[0263] Isopropyl alcohol 30.61 parts by mass Silica sol 4.15 parts by mass (silica sol with an average particle size of 100 nm, solid content concentration of 10.5% by mass)
[0264] PU-4WD 8.13 parts by mass (solid content concentration 35.0% by mass)
[0265] PEs-WD 3.79 parts by mass
[0266] (Solid content concentration: 25.0 mass%)
[0267] C-1WD 8.43 parts by mass (solid content concentration 30.0% by mass)
[0268] Surfactant 0.50 parts by mass (silicone-based, solid content concentration 10.0% by mass)
[0269] High boiling point solvent 0.34 parts by mass
[0270] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0271] (Examples 6, 7, 8, 9)
[0272] A highly adhesive polyester film was obtained in the same manner as in Example 2 except that the resin used was changed to the resin described in Table 1.
[0273] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0274] (Example 10)
[0275] A highly adhesive polyester film was obtained in the same manner as in Example 1 except that the crosslinking agent used was changed to C-2WD and a coating liquid prepared as follows was used.
[0276] Water 45.18 parts by mass
[0277] Isopropyl alcohol 30.57 parts by mass Silica sol 4.15 parts by mass (silica sol with an average particle size of 100 nm, solid content concentration of 10.5% by mass)
[0278] PU-4WD 10.83 parts by mass (solid content concentration 35.0% by mass)
[0279] C-2WD 8.43 parts by mass (solid content concentration 30.0% by mass)
[0280] Surfactant 0.50 parts by mass (silicone-based, solid content concentration 10.0% by mass)
[0281] High boiling point solvent 0.34 parts by mass
[0282] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0283] (Example 11)
[0284] A highly adhesive polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent used was changed to the crosslinking agent described in Table 1 in the same manner as in Example 10.
[0285] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0286] (Example 12)
[0287] A highly adhesive polyester film was obtained in the same manner as in Example 2 except that the resin used was changed to the resin described in Table 1.
[0288] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0289] (Examples 13 and 14)
[0290] Evaluation was performed in the same manner as in Example 1, except that the functional layer described in Table 1 was provided on the highly adhesive polyester film produced in the same manner as in Example 2. The evaluation results are as described in Table 1.
[0291] (Comparative Examples 1, 2, 3, 4, 5)
[0292] The resin and crosslinking agent shown in Table 1 were selected, and a coating liquid was prepared in the same manner as in Example 2. Next, in the same manner as in Example 1, a highly adhesive polyester film was obtained.
[0293] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0294] (Comparative Example 6)
[0295] A highly adhesive polyester film was obtained in the same manner as in Example 1 except that a coating liquid having the following composition was adjusted.
[0296] Water 31.58 parts by mass
[0297] Isopropyl alcohol 29.79 parts by mass Silica sol 16.17 parts by mass (silica sol with an average particle size of 100 nm, solid content concentration 10.5% by mass)
[0298] PU-11WD 5.62 parts by mass (solid content concentration 35.0% by mass)
[0299] PEs-WD 11.08 parts by mass (solid content concentration 25.0% by mass)
[0300] C-4WD 5.20 parts by mass (solid content concentration 40.0% by mass)
[0301] Surfactant 0.30 parts by mass (silicone-based, solid content concentration 10.0% by mass)
[0302] High boiling point solvent 0.26 parts by mass
[0303] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film to which a functional layer was provided was obtained in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0304] [Table 1]
[0305]
[0306] Industrial Applicability
[0307] According to the present invention, a highly adhesive polyester film which ensures the close adhesion reliability after being left in a high-temperature and high-humidity environment for a long period of time can be provided, and it is easier to apply to optical applications and the like.
Claims
1. An adhesive polyester film, comprising a coating layer on at least one surface of the polyester film, wherein the coating layer is formed from a composition comprising a polycarbonate polyurethane and a blocked isocyanate crosslinking agent, wherein the blocked isocyanate crosslinking agent is selected from an allophanate, a biuret or an adduct of hexamethylene diisocyanate, and the content of normal hexamethylene chains present at the α-position of carbonate bonds in the polycarbonate polyurethane is 3% by mass or more and 20% by mass or less relative to the mass of the polycarbonate polyurethane.
2. The highly adhesive polyester film according to claim 1, wherein The content of the n-hexanediol component in 100 mol % of the diol component in the polycarbonate diol constituting the polycarbonate polyurethane is 5 mol % or more and 30 mol % or less.
3. The highly adhesive polyester film according to claim 1 or 2, wherein The melting point of the polycarbonate diol constituting the polycarbonate polyurethane is 10° C. or higher.
Citation Information
Patent Citations
Easily-adhesive optical polyester film
JP2011168053A
Laminated polyester film
JP2011246663A
Laminated polyester film
JP2013063610A
Highly adhesive polyester film
CN102497985A
Packaging material, packaging container, and method for producing recycling base material
JP2021088408A